Predictors of women's participation in livelihood/entrepreneurial activities - Malicdem, Eleanor A.; Bongga, Demetria C. (2003)
Two hundred thirty (230) women coming from five barangays in Area 9, District II of Quezon City were interviewed to determine the predictors of the extent of women's participation in entrepreneurial or livelihood activities. The explanatory (independent) variables used in this study were categorized into three: pull factors, push factors and other factors. The pull factors included access to credit, awareness and availment of support and personal entrepreneurial characteristics. The push factors included income, household size and civil status. Other factors were age, education and consent of husband. The extent of women's participation was categorized into two measures: qualitative and quantitative. The qualitative measures included the nature and type of business and passion. The quantitative measures included capital investment and size of manpower. Simple random sampling was used to come up with the number of respondents for the interview. Responses of the respondents were subjected to frequency and central tendencies analyses to come up with a profile of a typical woman entrepreneur. Correlation analyses were used in preparation for the logistic regression involving qualitative measures and explanatory variables. Logistic regression was used in order to determine the likelihood of a woman entrepreneur choosing a certain type of business given, a set of explanatory variables. On the other hand, to test the significance of the explanatory variables as predictors of the quantitative measures of extent of participation, linear regression was used. Here, the dependent variables, namely starting capital and total number of employees were regressed against selected explanatory variables. Based on the results, a typical Filipino woman entrepreneur in the study can be described as married, 41 years old and with a high school education. She has a family size of five members with four grown-ups, no preschooler or an older person to attend to. There are at least two members in the family who are earning a living. She belongs to a low-income group, shown by a monthly income of Php 12,000. Her business is mainly associated with food, particularly street food vending. Her typical starting investment ranges from Php 2,000 to Php 10,000. More often, she does not employ the services of paid laborers in the business. In the logistic regression, household size, access to credit and the number of adolescent in the household predicted the women's choice of business type. In the regression analysis, high school and college education as well as household income predicted the women's starting capital while number of adolescent members predicted the total number of employees involved in the business.
Thesis (Ph.D. Home Economics)--University of the Philippines, Diliman.
Keywords: Women in development -- Philippines -- Quezon City; Businesswomen -- Philippines -- Quezon City; Women -- Philippines -- Quezon City -- Social conditions